Arisan Kurban dalam Perspektif Hukum Islam - Rosmita Rosmita; Zulfiah Sam; Isra ‘Aini; Nasaruddin Nasaruddin (AL-KHIYAR: Jurnal Bidang Muamalah dan Ekonomi Islam, 2023)
This study aims to provide clarity regarding the law on the implementation of the sacrificial arisan in the view of Islamic law. This research uses a qualitative approach with library research methods and descriptive analysis. The results of this study indicate that the opinion of the majority of scholars regarding the law of sacrificial worship is that sacrifice is not obligatory but is sunnah for those who can afford it. For people who are less able but have a great desire to get closer to Allah through the performance of sacrificial services, there is nothing wrong with following the arisan method which includes elements of debt and credit. With a note if there is a guarantee of the ability to pay it. The implementation of the sacrificial arisan which is carried out by some members of the community is legally permissible or permissible because it fulfills the terms and pillars of the contract. The implementation of the qurban gathering is a new problem in muamalah which did not exist before at the time of the prophets and companions and has not been mentioned in the Qur'an or hadith, so it is returned to the original law of a problem. It is permissible as long as there is no reason to forbid it. The qurban gathering carried out by some people has fulfilled the principles of muamamalah, namely the principle of mutual consent between all parties. In carrying out this sacrificial arisan, it brings many benefits to people who are less fortunate but have a great desire to carry out sacrificial worship in order to draw closer to Allah. Another benefit that is also found in the implementation of this sacrificial arisan is that it can be a means to get closer to Allah and to establish friendship between all members of the arisan group. Given the many benefits derived from the implementation of the sacrificial arisan.